Aligning graphene sheets in aerogel-based composites for enhanced electromagnetic interference absorption - Seo, Ji Hun; Yang, Hyun Seong; Seo, Min Ho; Kim, Seon Joon; Lee, Juyun; Kee, Seyoung; Habibpour, Saeed; Lim, Sung-Nam; Ahn, Wook; Jun, Yun-Seok (Pergamon Press Ltd., 2025)
This study investigates graphene aerogel-based polydimethylsiloxane (PDMS) composites designed to improve electromagnetic interference (EMI) absorption. These composites are fabricated by infiltrating PDMS into graphene aerogel produced by uni-directional freezing and thermal reduction. This results in a graphene structure with highly aligned orientations. The composites in longitudinal directions exhibit a shielding effectiveness by absorption (SEA) of 8.6 dB/mm and a shielding effectiveness by total (SET) of 11.5 dB/mm in 8.2-12.4 (X-band) frequency range. On the other hand, the transverse direction shows a lower EMI shielding capability with a SEA of 4.5 dB/mm and a SET of 6.7 dB/mm. These are attributed to the fact that the aligned orientation of the fillers increased the internal multiple scattering of incident electromagnetic wave, which increases the propagation path and energy attenuation. These results demonstrate that controlling the filler orientation can significantly increase the EMI performances of graphene/PDMS composites.